(untitled) (Pravaha, 2021)
This study attempts to evaluate knowledge dissemination in the Nepalese telecom industry. It is based on cross section analysis of 85 observations for analyzing relationship between knowledge dissemination statuses in Nepalese telecom industry. The study is based on Kohli et al. (1993) and Daroch (2003) methodologies. Survey instruments are organized into one part and four factors. Spearman Rank Correlation, Analysis of variance (ANOVA), Cronbach’s alpha etc. is used for data analysis. The valid response rate of 70.7 % is found. Among the factors that designed for knowledge dissemination and combination has less mean score and socialization has higher mean score than the other factors. In case of socialization, Nepalese Telecom industry analyzes the social contribution of their products or services. Employees of Nepal Telecom has rated higher mean value in knowledge dissemination practices, which means Nepal Telecom appeared better in knowledge dissemination practices than Ncell. There is a significant difference between Nepal Telecom and Ncell in term of knowledge dissemination. Nepal Telecom has better KD (Knowledge Dissemination) practices. The correlation matrix is created to determine the extent to which the components or research variables are related.